Short-term effects of alcohol detoxification on cardiovascular, hematological, and oxidative stress biomarkers: A prospective cohort study - Ashraf Mahmoud Emara; Anoud Maseer Ateeq Alshammari; Ahmad H. Alhowail; Rehab Mohamed Elgharabawy (PLoS ONE, 2026)
Introduction Chronic alcohol consumption induces multisystem dysfunction, including cardiovascular instability, hematological alterations, and oxidative stress imbalance. However, the extent of short-term recovery following structured detoxification remains incompletely characterized. Objective To evaluate the short-term effects of a standardized inpatient alcohol detoxification protocol on cardiovascular, hematological, and oxidative stress biomarkers. Methods A prospective observational before-and-after cohort study was conducted on 75 male participants, including 50 patients with alcohol use disorder and 25 healthy controls. Patients underwent a 21-day inpatient detoxification program comprising pharmacological stabilization and nutritional rehabilitation. Clinical and biochemical parameters—including body mass index, vital signs, lipid profile, complete blood counts, troponin-I, and oxidative stress markers (TBARS, glutathione peroxidase, and catalase)—were assessed at baseline and post-treatment. Results Compared to healthy controls, treatment-naïve patients with alcohol use disorder (AUD) exhibited significantly elevated baseline levels of lymphocytes, total cholesterol, low-density lipoprotein (LDL), thiobarbituric acid reactive substances (TBARS), and catalase (CAT), alongside significantly lower heart rate (HR), systolic blood pressure (SBP), neutrophil-to-lymphocyte ratio (NLR), high-density lipoprotein (HDL), and glutathione peroxidase (GPx). Baseline anthropometric, vital, hematological, and metabolic markers—including BMI, diastolic blood pressure (DBP), hemoglobin (Hb), platelets, total white blood cell count (WBCs), cardiac troponin-I (cTnI), and triglycerides—showed no statistically significant differences. Following a 21-day inpatient detoxification protocol, post-treatment assessments revealed significant increases in red blood cell parameters (RBCs, Hb, Hct), neutrophils, lymphocytes, NLR, and HDL. Conversely, standard detoxification induced significant reductions in cardiovascular, lipid, and oxidative stress indices, specifically HR, SBP, mean corpuscular volume (MCV), total WBCs, cTnI, total cholesterol, triglycerides, TBARS, and CAT. No significant post-treatment alterations were observed in BMI, DBP, platelet counts, LDL, or GPx. Conclusion Short-term alcohol detoxification leads to partial recovery of cardiovascular and hematological parameters, while oxidative stress markers show limited normalization within the 21-day period. These findings highlight differential recovery patterns across biological systems following early abstinence.